The Practical Criteria of Accuracy of Forensic Investigations in Statistical Values - I. A. Grigor’ev (Теория и практика судебной экспертизы)
The article presents a scientific and practical analysis of ensuring the accuracy of forensic experts’ opinions. It is shown that Russian substantive and procedural legislation needs improvements in the part of the inclusion of the criteria for assessing expert opinions’ accuracy. It has become necessary to develop more explicit criteria for the appointment of additional and re-examinations. New legal definitions are required to establish the cases when probabilistic and evaluative characteristics may be the ground for doubts in the accuracy of an expert’s opinions. Basing on the official statistics of expert errors ascertained by justice, the author proposes to define the criteria of expert opinions’ accuracy in the legislation.